Implementasi Nilai-Nilai Pancasila dalam Pelayanan di Puskesmas Nabarua Tahun 2023 - Marthen Toding (STIKES Columbia Asia Medan, 2024)
Pancasila values ​​are not only implemented at that time but are preserved every day. As the basis of the Indonesian nation and state, Pancasila is essentially derived from cultural values, not just as reflections or thoughts of individuals like other foundations in the world, religious values ​​contained in the outlook on life of the Indonesian nation before the founding of a country. The aim of the research is to see the implementation of these values. -Pancasila values ​​in services at the Nabarua Health Center. The method used in this research is literature study (data collection, literature references related to the implementation of Pancasila values) with a case study type of research using research. Qualitative descriptive approach. The results of the research. The implementation of Pancasila values ​​is reflected in five principles, starting from the value of God to the value of Justice which is implemented in health services for medical record officers. The first principle is demonstrated by the activity of greeting and saying hello, the second principle is an attitude of helping each other through humanitarian activities such as Health Services for Children, Toddlers, Adults and the Elderly. The third principle is to join a professional organization. The fourth principle is demonstrated by providing opinions during evaluation meetings held every month at the Community Health Center. The fifth principle is implementing working relationships between medical record officers in accordance with the professional code of ethics. The suggestion in this research is to apply Pancasila values ​​at the Community Health Center, there are internal obstacles such as officers being late in attending the morning roll call and some officers being unable to attend the evaluation meeting which is held once a month. The head of the Community Health Center has an important role in applying Pancasila values ​​to medical records officers. So, the head of the community health center and his staff must be more able to provide motivation, support and examples for officers in implementing the values ​​of Pancasila.